ANDROID-BASED MONEY TRACKER APPLICATION INFORMATION SYSTEM USING FLUTTER - Rafi Ar Rafii; Yulian Findawati; Uce Indahyanti; Arif Senja Fitrani (Journal of Artificial Intelligence and Digital Economy, 2025)
Objective: This study aims to design and develop a personal finance recording application for Android using the Flutter framework to enhance user convenience in managing daily financial transactions. Method: The research employed a system development methodology comprising requirement analysis, interface design, implementation using Flutter, and integration of a local SQLite database through the Drift package. Results: The resulting application, Money Tracker, enables users to record financial activities in real time, generate visual reports through pie chart representations, and utilize a chatbot feature for interactive assistance. The application demonstrates efficiency, user-friendliness, and functional reliability in supporting personal financial management. Novelty: This study contributes an innovative integration of Flutter and Drift-based local database technology with interactive visualization and chatbot support, offering a comprehensive and accessible solution for managing personal finances on mobile platforms.